Iatrogenic vertebral artery pseudoaneurysm: US, CT and MRI findings - Cihangiroglu, M; Rahman, A; Yildirim, H; Burma, O; Uysal, H (Elsevier Ireland Ltd, 2002)
Vertebral artery pseudoaneurysm (VAP) is the result of the penetrating neck trauma, chiropractic manipulation, vasculopathies and rarely iatrogenic due to internal jugular vein (IJV) catheterization. It should be identified and treated immediately because of its potential risk of rupture. We present a case of a right VAP resulting from jugular vein catheterization. with the Doppler ultrasonography (US), Computed tomography (CT) and magnetic resonance imaging (MRI) findings. Although angiography is a well known gold standard modality. Doppler US, CT and MRI findings can be sufficient to demonstrate VAP. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: computed tomography; magnetic resonance imaging; ultrasonography; vertebral artery; pseudoaneurysm